As tendências pedagógicas e o ensino de Geografia: entre rupturas e continuidades - Souza, José Vitor Rossi [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
School practices are permeated by different objectives, means and theoretical and methodological assumptions, and the representations of these concepts translate philosophical concepts about the world. These pedagogical references act, intentionally or not, in the concepts of world/society, in the teaching methods used and in the evaluation methods, including having school institutions as spaces of great importance in the effectiveness of pedagogical conceptions. Such variables are linked to different pedagogical tendencies and, historically, several of them have influenced and influence the teaching of Geography, such as the traditional, scholar, technician and historical-critical. Therefore, this research seeks to review the trajectory of School Geography in order to demonstrate how the teaching of Geography, in its theoretical foundations and discourses about the practice, is related to pedagogical tendencies. In addition, more specifically, it also aims to discuss how the teaching of this discipline has been marked by ruptures and continuities for over more than two centuries, emphasizing that it is currently permeated, synchronously, by various tendencies, showing relationships between the new and the old. As a research methodology, of an exploratory and qualitative nature, a wide bibliographic review was carried out (based on authors from Didactics, Philosophy of Education, History of Education, Teaching of Geography, among others) and also documentary analysis. As a starting point, the systematization of tendencies was chosen: traditional, renewed non-directive, renewed progressive, technicist, liberating, libertarian and social-critical of the contents. Subsequently, these tendencies were linked to the analysis of the contents of Geography, to textbooks, to the study proposals of the milieu / fieldwork and also to the curricular guidelines (CENP Proposal, National Curriculum Parameters and Common Curricular National Base). As a result, it was concluded that there are no isolated periods with regard to the influence of certain tendencies and that, nowadays, there is a recovery of assumptions from the past, which are widespread as being innovative. Finally, the relevance of this work is justified, among other reasons, by the fact that it provides a subsidy for a more conscious teaching practice about its pedagogical and epistemological foundations and also to assist in the search for the origins of ideas that circulate about the teaching of Geography.

As práticas escolares são perpassadas por diferentes objetivos, meios e pressupostos teórico-metodológicos, sendo que as representações dessas concepções traduzem concepções filosóficas sobre o mundo. Esses referenciais pedagógicos atuam, intencionalmente ou não, nas concepções de mundo/sociedade, nos meios de ensino utilizados e nos métodos avaliativos, inclusive tendo as instituições escolares como espaços de grande importância na efetivação de concepções pedagógicas. Tais variáveis estão ligadas a diferentes tendências pedagógicas e, historicamente, diversas delas influenciaram e influenciam o ensino de Geografia, como a tradicional, escolanovista, tecnicista e a histórico-crítica. Diante disso, essa pesquisa busca fazer uma revisão sobre a trajetória da Geografia Escolar com o intuito de demonstrar como o ensino de Geografia, em seus fundamentos teóricos e discursos sobre a prática, se relaciona com as tendências pedagógicas. Além disso, mais especificamente, objetiva-se também discutir como o ensino dessa disciplina tem sido marcado por rupturas e continuidades ao longo de mais de dois séculos, ressaltando que atualmente é perpassado, sincronicamente, por várias tendências, evidenciando relações entre o novo e o velho. Como metodologia de investigação, de cunho exploratório e qualitativo, foi realizada uma ampla revisão bibliográfica (baseada em autores da Didática, Filosofia da Educação, História da Educação, Ensino de Geografia, entre outros) e também a análise documental. Como ponto de partida, escolheu-se a seguinte sistematização das tendências: tradicional, renovada não-diretiva, renovada progressivista, tecnicista, libertadora, libertária e crítico-social dos conteúdos. Posteriormente, essas correntes foram articuladas à análise dos conteúdos de Geografia, aos livros didáticos, às propostas de estudo do meio/trabalho de campo e também às orientações curriculares (Proposta da CENP, Parâmetros Curriculares Nacionais e Base Nacional Comum Curricular). Como resultados, concluiu-se que não há períodos estanques no que se refere à influência de determinadas tendências e que também, atualmente, há um resgate de pressupostos do passado, que são difundidos como sendo inovadores. Por fim, a relevância desse trabalho se justifica, entre outros motivos, pelo fato de proporcionar um subsídio para uma prática docente mais consciente sobre seus fundamentos pedagógicos e epistemológicos e também para auxiliar na busca das origens de ideias que circulam sobre o ensino de Geografia.
The pedagogical tendencies and Geography teaching: between ruptures and continuities
Keywords: Geography teaching; Textbooks; Didactics; Pedagogical tendencies; School geography; Ensino de Geografia; Tendências pedagógicas; Livros didáticos; Geografia escolar; Didática